DETEKSI KANDUNGAN GAS KARBON MONOKSIDA (CO) HUBUNGAN DENGAN KEPADATAN LALU-LINTAS DI MEDAN SUNGGAL, KOTA MEDAN - ashar hasairin; Rosliana Siregar (JBIO: jurnal biosains (the journal of biosciences), 2018)
The aim of this study to determine: a) the consentration of carbon monoxide in the air in District Medan Sunggal, b) the relationship between traffic density and the concentration of CO (Carbon Monoxide) in Medan Sunggal, c) is there the relationship between the condition of physical and chemical environment on the concentration CO in Medan Sunggal. This study was conducted in December 2013- February 2014 in the three location, they are: 1) Jl. Arten Ringroad, 2) Jl. TB Simatupang, 3) Jl. Setia Budi, air analysis performed in BTKL PP Medan. The design of this study using the pearson product moment correlation. The parameter measured were the number of level of CO, the physical-ehemical properties and the totality of traffic density. The research findings indicated that: the highest level of CO was in Jl. Setia Budi with 17 ppm while in the Jl. TB Simatupang was 11 ppm and in the Jl. Arten Ringroad 8 ppm. There is a significant relationship between traffic density with the content of CO levels with the value r=0,9. The correlation is very high, the correlation is positive significant. By counting using the pearson product moment analysis was obtained tcont (5,4)  ≥  t table(1,895). There is relationship between traffic density and the levels of CO in the air. While the dampness and wind speed on the consentration of CO is found negative correlation. The correlation of temperature on the concentration of CO is r=0,9, but there is not significant correlation by t hitung(2,1)  ≤ dari  t tabel (6,314).